DARI ORIENTASI ESG KE WORD OF MOUTH: PERAN MEDIASI KEPERCAYAAN KONSUMEN DAN PENCIPTAAN NILAI PELANGGAN - Rinaldi Bursan; Prakarsa Panjinegara; Faila Shofa; Doni Sagitarian Warganegara (Nusantara Hasana Journal, 2026)
Environmental, Social, and Governance (ESG) orientation is increasingly being adopted by companies as a sustainability strategy, yet understanding how this orientation translates into consumer behavioral responses remains limited. This study aims to explain the processual mechanisms linking ESG orientation to consumer word of mouth through the mediating role of consumer trust and customer value creation. Drawing on commitment–trust theory and the customer value creation literature, this study develops a conceptual model that positions customer trust and value as key mechanisms in this relationship. Data were collected through a survey of consumers who had experience with companies that actively communicate ESG practices and were analyzed using partial least squares structural equation modeling (PLS-SEM). The analysis results indicate that ESG orientation positively influences consumer trust, which in turn drives customer value creation. Customer value creation proved to be a significant predictor of word of mouth. Furthermore, the results of the indirect effects test confirmed that consumer trust and customer value creation, respectively, mediate the relationship between ESG orientation and word of mouth. This study contributes to the sustainable marketing literature by demonstrating that ESG orientation does not operate solely as a symbolic signal, but rather as a relational mechanism that shapes consumer values ​​and behavior. From a managerial perspective, these findings emphasize the importance of managing ESG as a trust-based and customer experience strategy to drive sustainable consumer advocacy.